Proteomic characterization of hippocampus of chronically socially isolated rats treated with fluoxetine: depression-like behaviour and fluoxetine mechanism of action - Peric, Ivana; Costina, Victor; Findeisen, Peter (Neuropharmacology, 2018)
Due to the severity of depressive symptoms, there remains a necessity in defining the underlying mechanisms of depression and the precise actions of antidepressants in alleviating these symptoms. Proteomics is a powerful and promising tool for discovering novel pathways of cellular responses to disease and treatment. As chronic social isolation (CSIS) is a valuable animal model for studying depression, we performed a comparative subproteomic study of rat hippocampus to explore the effect of six weeks of CSIS and the therapeutic effect of chronic fluoxetine (Flx) treatment (last three weeks of CSIS; 15mg/kg/day). Behaviorally, Flx treatment normalized the decreased sucrose preference and increased marble burying results resulting from CSIS, indicative of a FLX-induced attenuation of both anhedonia and anxiety. An analysis of cytosolic and nonsynaptic mitochondrial subproteome patterns revealed that CSIS resulted in down-regulation of proteins involved in mitochondrial transport and energy processes, primarily tricarboxylic acid (TCA) cycle and oxidative phosphorylation. Chronic Flx treatment resulted in an up-regulation of CSIS-altered proteins and additional expression of other transporter and energy-involved proteins. Immunohistochemical analysis revealed hippocampal subregion-specific effects of CSIS and/or Flx treatment on selective protein expressions.
Gesehen am 13.10.2020